Visual art plays a special role in human life - Oydinov Sharip Baxronovich (Zien Journals, 2022)
This scientific article discusses the high level of development of fine arts in our country, the unique role of fine arts in human life. It also covers the basics of teaching the secrets of painting, getting acquainted with works of fine art, and overcoming some of the problems that arise in artistic analysis.
Keywords: Fine Arts; Afrosiyob; Bolaliktepa; Varakhsha